Study of erosion efficiency of polymers and polymer composites - Arjula S.; Harsha A.P. (My University, 2025)
The erosion efficiency (η) of polymers and polymeric composites has been evaluated by collecting the available data from the literature pertaining to solid particle erosion under normal impact conditions. The objective of this paper is to show the usefulness of the η parameter to identify various mechanisms in solid particle erosion. The erosion efficiency map is plotted, which indicates the influence of hardness of various polymers and polymer composites on their erosion resistance. The various regimes and demarcations that correspond to erosion efficiency of polymers and polymeric composites have been highlighted in the map. Erosion response, erosion efficiency and wear mechanisms of various polymers and composites have been discussed and compared with the available data in the literature. © 2005 Elsevier Ltd. All rights reserved.